PEMBERDAYAAN SIKAP PEDULI LINGKUNGAN MELALUI PROGRAM TADABUR ALAM PADA SISWA MADRASAH ALIYAH (MA) MA'ARIF DURENSEWU PANDAAN - Nahdiyah, Dini; Wati, Silvia Yuniar; Taqwa, Kaulia; Nuzula, Firdausi; Aprilia, Sofia Sasa Bella; Kirom, Askhabul (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract An attitude of caring for the environment is an attitude that must be instilled and introduced to every child from an early age to adulthood until it becomes a habit and obligation to protect and preserve the environment. This empowerment aims to produce environmentally caring behavior among MA Ma'arif Durensewu Pandaan students. This community service activity is carried out using the 5t PAR method (to know, to understand, to plan, to act, to reflect). The results of the empowerment are in the form of Socialization of the Tadabbur Alam Program, Introducing the Relationship between Humans and Nature, 1st Education on how to manage used bottles, 2nd Education on caring for the school environment, Assistance with tadabbur alam. Thus, through the assistance provided students to MA Ma'arif Durensewu Pandaan students become intelligent in science, but also have a deep sense of concern for nature conservation. Keywords: empowerment, Tadabbur Nature, Environmental Care Attitude   Abstrak Sikap peduli lingkungan merupakan sikap yang harus ditanamkan dan dikenalkan pada setiap anak sejak usia dini hingga dewasa hingga menjadi suatu kebiasaan dan kewajiban menjaga dan melestarikan lingkungan hidup. Pemberdayaan ini bertujuan untuk menghasilkan perilaku peduli lingkungan di kalangan siswa Madrasah Aliyah (MA) Ma’arif Durensewu Pandaan. Kegiatan pengabdian kepada masyarakat ini dilaksanakan dengan metode 5t PAR (to know, to understand, to plan, to act, to reflect). Hasil dari pemberdayaan tersebut berupa Sosialisasi Program Tadabbur Alam, Pengenalan Hubungan Manusia dan Alam, Edukasi I cara mengelola botol bekas, Edukasi II peduli lingkungan sekolah, Pendampingan tadabbur alam. Dengan demikian, melalui bantuan yang diberikan siswa MA Ma'arif Durensewu Pandaan menjadi siswa yang cerdas dalam bidang sains, serta memiliki rasa kepedulian yang mendalam terhadap kelestarian alam. Kata Kunci: Pemberdayaan, Alam Tadabbur, Sikap Peduli Lingkungan